Constraints in the growth of processed food sector and proposed export strategy: a case study of India. (5th January 2015) - Mahajan, Rajneesh; Garg, Suresh; Sharma, P.B.
The objective is to identify the constraints in growth of the processed food sector (PFS) and propose a strategy for boosting exports of processed food from India. An empirical research was conducted. The questionnaire was administered to gather 252 responses. Fifteen PFS constraints were identified, such as lack of traceability (LTE), weak HACCP implementation (WHAP), lack of end to end cold chain (LEC), limited single product cold storage (LSPS), high level of wastages from source to plant (HLW), weak governmemt policies (WGRP), limited warehousing (LWA), lack of quality and connectivity of vehicles (LQCV), weak road transportation (WRT), lack of skilled workers (LSW), inadequate application of IT tools (IAIT), lack of world class quality (LWQ), long and fragmented logistics (LFA), inadequate research and development (IRD), and lack of good technology (LGT). The proposed strategy is to improve post harvest techniques in order to achieve the desired high performance of Indian PFS exports. The present research will be useful for the companies, academia and policy makers.